Des érudits du Siècle d’or au travail : les recherches de Jerónimo Zurita et Juan Bautista Pérez sur la Divisio Wambæ - David Gazel (E-Spania)
Since Pelayo de Oviedo, if not earlier, the Divisio Wambæ has continuously excited the curiosity of generations of historians. At the end of the 16th century, this text captured the attention of great scholars such as Jerónimo Zurita, Juan Bautista Pérez, Andreas Schott, Ambrosio de Morales, García de Loaysa, Bernado de Brito or Juan de Mariana. The recent discovery by Francisco Bautista of a hitherto unknown testimony gave us the opportunity to clarify relationships between works performed by the three first mentioned and the development of what Vázquez de Parga described as a «primer esbozo de edición crítica» of Divisio Wambæ.